VMware as an Intermediate Platform between Windows 7 and Linux Fedora 15 for Real-Time Malaysian Sign Language Translator - Bilal, Sara Mohammed Osman Saleh; Nassr, Rasheed; Akmeliawati, Rini (2014)
This research introduces a virtual interface between Windows 7 and LINUX Fedora 16 based on Virtual Machine ware (VMware) for real-time Malaysian Sign Language (MSL) translation into text and/or voice (in English). The developed method is based on HTK, Gt2k under LINUX Fedora 16 and VC++ 2010 and OpenCV pre 1.1 library under Windows7. The communication between client (Windows7) and server (LINUX Fedora 16) has been established using VMware. The main significance of this approach is that the best characteristics of both operating systems LINUX Fedora 16 and Windows7 have been utilized. Under Windows7, Visual C++ 2010 combined with OpenCV pre 1.1 library supports video processing algorithms and has a power graphical user interface. Meanwhile, the Gt2k for gesture recognition is fully supported under LINUX. Therefore, a client/server technology has secured much time during the MSL recognition system development and helped in terms of algorithms enhancement